2019
DOI: 10.19045/bspab.2019.80140
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of Luma apiculata against resistant strains of Staphylococcus aureus and Klebsiella pneumoniae

Abstract: Bacterial resistance is the mechanism through which the bacteria can decrease the action of antimicrobial agents. Studies have reported an antimicrobial action of Luma apiculata, however, there are no in vitro studies demonstrating the effect of this plant against multidrug-resistant bacteria. The objective of this study was to explore the antimicrobial properties of alcoholic extract of Luma apiculata against standard multi-resistant bacterial pathogens. Multidrug-resistant strains of Staphylococcus aureus AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
0
0
1
Order By: Relevance
“…Pseudomonas aeruginosa and St. aureus, establishing for the latter an IC50 (median inhibitory concentration) between 0.354 and 0.385 mg/mL [20]. On the other hand, Treulen et al (2019) established the MIC of an Arrayan extract for St. aureus between 1 and 10 mg/mL, consistent with our study, where a dose used for BC of 0.8% w/v (8 mg/mL) was established [34]. In a similar manner, Araya-Contreras et al ( 2019) determined that hexane Arrayan extracts showed antibacterial activity against St. aureus, St. epidermidis, I. saprophyticus, Enterococcus sp., A. baumanii, Pseudomona aeruginosa, and E. coli at concentrations greater than 100 µg/mL [19].…”
Section: Viktorová Et Al (2020) Studied the Antimicrobial Effects Of ...mentioning
confidence: 99%
“…Pseudomonas aeruginosa and St. aureus, establishing for the latter an IC50 (median inhibitory concentration) between 0.354 and 0.385 mg/mL [20]. On the other hand, Treulen et al (2019) established the MIC of an Arrayan extract for St. aureus between 1 and 10 mg/mL, consistent with our study, where a dose used for BC of 0.8% w/v (8 mg/mL) was established [34]. In a similar manner, Araya-Contreras et al ( 2019) determined that hexane Arrayan extracts showed antibacterial activity against St. aureus, St. epidermidis, I. saprophyticus, Enterococcus sp., A. baumanii, Pseudomona aeruginosa, and E. coli at concentrations greater than 100 µg/mL [19].…”
Section: Viktorová Et Al (2020) Studied the Antimicrobial Effects Of ...mentioning
confidence: 99%
“…(i) Prueba de sensibilidad de S. aureus a cefoxitina (discos con 30 ug); (ii) Prueba de sensibilidad a vancomicina. Prueba E (Epsilometer-Test) para la cuantificación de la susceptibilidad de los microorganismos, determinando la concentración mínima inhibitoria (MIC)(Treulen et al, 2019).…”
unclassified